GPVI oligomerisation in cell lines and platelets - Berlanga, Oscar (2007)
BACKGROUND: Glycoprotein VI (GPVI) is a physiological receptor for collagen expressed at the surface of platelets and megakaryocytes. Constitutive dimerisation of GPVI has been proposed as necessary for the interaction with collagen, although direct evidence of dimerisation has not been reported in cell lines or platelets. OBJECTIVES: To investigate oligomerisation of GPVI in transfected cell lines and in platelets under nonstimulated conditions. METHODS AND RESULTS: By using a combination of molecular and biochemical techniques, we demonstrate that GPVI association occurs at the surface of transfected 293T cells under basal conditions, through an interaction at the extra-cellular domain of the receptor. Bioluminescence resonance energy transfer was used to confirm oligomerisation of GPVI under these conditions. A chemical cross-linker was used to detect constitutive oligomeric forms of GPVI at the surface of platelets, which contain the FcR γ-chain. CONCLUSIONS: The present results directly demonstrate GPVI-FcR γ-chain oligomerisation at the surface of the platelet, and thereby add to the growing evidence that oligomerisation of GPVI may be a pre-requisite for binding of the receptor to collagen, and therefore for proper functioning of platelets upon vascular damage.